Makna Tradisi Kasaraka pada Masyarakat Etnik Muna di Desa Kasakamu, Kecamatan Kusambi, Kabupaten Muna Barat - Wa Ode Sriana Wati; La Niampe; Komang Wahyu Rustiani (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2022)
The tradition of kasaraka is a tradition practiced by the ethnic group of Muna when they are about to harvest corn, however, its implementation has been decreasing. This research aims to describe the process of the kasaraka tradition and analyze the meanings contained in the implementation of the kasaraka tradition among the ethnic Muna. The theory used in this research is Roland Barthes' semiotics theory using descriptive qualitative research method. The results of the research show that the process of the kasaraka tradition consists of three stages: preparation stage, implementation stage, and final stage. The meanings contained in the kasaraka tradition are viewed from the process and tools used in the kasaraka tradition.